2019
DOI: 10.1088/1748-9326/ab51b6
|View full text |Cite
|
Sign up to set email alerts
|

On the use of indices to study extreme precipitation on sub-daily and daily timescales

Abstract: While there are obstacles to the exchange of long-term high temporal resolution precipitation data, there have been fewer barriers to the exchange of so-called 'indices'. These are derived from daily and sub-daily data and measure aspects of precipitation frequency, duration and intensity that could be used for the study of extremes. This paper outlines the history of the rationale and use of these indices, the types of indices that are frequently used and the advantages and pitfalls in analysing them. Moving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 57 publications
(49 reference statements)
2
56
0
Order By: Relevance
“…The ETCCDI indices have a long heritage in their use for monitoring, analyzing, and projecting moderate extreme events and absolute values (Alexander et al., 2019; Zhang et al., 2011). They are calculated from daily maximum and minimum temperature as well as daily precipitation amount.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…The ETCCDI indices have a long heritage in their use for monitoring, analyzing, and projecting moderate extreme events and absolute values (Alexander et al., 2019; Zhang et al., 2011). They are calculated from daily maximum and minimum temperature as well as daily precipitation amount.…”
Section: Datamentioning
confidence: 99%
“…For almost two decades, the former WMO/WCRP/JCOMM Expert Team on Climate Change Detection and Indices (ETCCDI) was one of the leading groups to develop a standard set of indices representing temperature and precipitation extremes for the terrestrial environment, representing 29% of the surface of the globe (Frich et al., 2002; Karl et al., 1999; Peterson, 2005). The development of these standard climate indices based on daily data has allowed derived products to be more easily and widely shared than the underlying measurements themselves (Alexander et al., 2019; Thorne et al., 2017; Zhang et al., 2011), because in many cases, these raw daily observations are not openly available. The ETCCDI facilitated several regional workshops, where representatives of National Meteorological and Hydrological Services (NHMSs) could attend and calculate the climate extremes indices from their daily data without needing to release those data publicly (Aguilar et al., 2009; Caesar et al., 2011; Donat et al., 2014; Peterson & Manton, 2008; Meteorological Service Singapore, 2019; Vincent et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The monthly and annual precipitation frequency was calculated using the R95p, CDD, Rx5day index, developed by ETCCDI (Expert Team on Climate Change Detection and Indices), using the ClimPACT2 index standardization software (Alexander and Herold, 2016). The definition of the indices (Zhang and Yang, 2004;Alexander, 2016 andAlexander et al, 2019) is shown in…”
Section: Determination Of Extreme Rainfall and Frequency Of Occurrencementioning
confidence: 99%
“…Understanding the spatiotemporal behavior of hydrometeorological events is of critical importance for water resource management including flood mitigation and response, ecosystem restoration, river and water supply reservoir recharge, and water quality impacts. Evaluating how hydrometeorological extremes have historically behaved, including variations in intensity, duration, and frequency is of upmost importance not only for current water resource management, but also to understand long-term climate impacts and provide accurate predictions of future behavior (Alexander et al, 2019;Maggioni and Massari, 2019;Mahbod et al, 2019;Tongal, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…More recent research, especially with long-term and climate change studies, have shifted to the use of standardized indices to allow for consistency between studies. These indices include the Expert Team on Climate Change Detection and Indices (ETCCDI), the Standardized Precipitation Index (SPI), the Standardized Precipitation, and Evapotranspiration Index (SPEI), and the Palmer Drought Severity Index (PDSI) which measure aspects of frequency (e.g., days above fixed thresholds), intensity (e.g., wettest day, average daily intensity), and duration (e.g., consecutive wet and dry days) based on daily precipitation measurements from in situ, satellite, and/or reanalysis datasets (Alexander et al, 2019;Qin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%